Community engagement to control dengue vector in two municipalities of Aragua State, Venezuela - Martínez, María; Mijares, Victor; Moreno, Nancy; Pérez-Ybarra, Luis; Herrera, Flor de María (Utan Kayu Publishing, 2023)
A safe and effective dengue vaccine is not ready yet; therefore, dengue prevention is necessary to control the spread of this infection. Lowering dengue disease depends on controlling mosquitoes by reducing Aedes habitats counting with community participation. We studied community participation on habitat reduction for immature stages of Aedes aegypti in two urban communities of the Aragua State from May 2009 to November 2018. The sample consisted of 100 houses of one community and 400 houses of the other. Fisher´s exact test was used to compare the proportions of positive houses or containers through the study period. House index, container index, and Breteau Index were calculated. The data were analyzed using Minitab 20.4 statistical software. The research team initiated the approach to the communities by contacting some of their natural leaders in January 2009. The methodological strategies included workshops, lectures, seminars, document and video reviews, practices, discussions, and knowledge sharing within and with the community. After six months of the intervention, a significant reduction in the Aedes larval indices was found in both communities and lasted for the entire study period. The intervention increased public consciousness and participation in dengue vector control measures in residential areas, and this behavior change was sustainable over time.